THE IMPACT OF HYPERTENSION STATUS ON SURVIVAL IN THE RUSSIAN FEDERATION. (April 2021) - Vladimir, Kutsenko; Balanova, Yulia; Imaeva, Asiia; Kapustina, Anna; Muromtseva, Galina; Evstifeeva, Svetlana; Karamnova, Natalya; Maksimov, Sergey; Yarovaya, Elena; Shalnova, Svetlana
Abstract : Objective: To evaluate associations between hypertension and mortality among the Russian population. Figure. No caption available. Design and method: A cross-sectional study Epidemiology of cardiovascular diseases in the RF (ESSE) was carried out in 14 regions of the Russian Federation (2012–13), response rate>80%. The prospective cohort included randomly selected males (N = 7243) and females (N = 11061) aged 25–64 (11 regions). Standard epidemiology methods and criteria were used. Arterial hypertension (AH) is defined as measured blood pressure (BP) of 140/90 mm Hg or greater and/or treatment with antihypertensive medications. Participants were divided into the four groups by BP levels and hypertension treatment: without hypertension (No AH), treated hypertensives who control their BP level (Controlling), hypertensives never treated (Untreated), and treated but not achieved target BP level (Not controlling). Endpoints were collected once every two years. The mortality follow-up period was 7 years, 397 deaths were observed. Statistical data was processed using R 3.6.1. We used Kaplan-Meier estimator and log-rank test to investigate the relationship between risk groups and survival. We assessed the same relationship using the age-adjusted Cox proportional hazards model. P < 0.05 was considered as significant. Results: During the follow-up period, there were 83 deaths from coronary heart disease, 39 deaths – cerebrovascular accident, 20 deaths – other CVDs, 255 deaths – non-CVD. The impact of hypertension on survival was found among males and among females (p < 0.0001 for both) (fig. 1 A, B). The most significant total mortality risk was noted in the «Not controlling» group (males OR: 1.83, females OR: 1.59) (fig. 1 C, D). Similar results were obtained for CVD mortality (males OR: 2.72, females OR: 3.23, p < 0.005 for both). The survival in groups «Controlling» and «Untreated» did not differ significantly. However, «Controlling» participants were older than «Untreated» participants and had a larger waist size, greater prevalence of hyperlipidemia, and diabetes mellitus. Conclusions: The presence of hypertension significantly increases the risk of death. Treated but BP uncontrolled hypertensive subjects had the highest mortality risk. The absence of differences between «Controlling» and «Untreated» participants is due to differences in age and comorbidities.